Veterinary support staff knowledge and perceptions of antimicrobial drug use, resistance, and stewardship in the United States - Gunn-Sandell, Lauren; Taylor, Daniel D.; Scallan Walter, Elaine (Frontiers in Veterinary Science, 2024)
Antimicrobial drug use (AMU) in veterinary medicine may contribute to antimicrobial resistant (AMR) infections in both animals and people. Efforts to improve AMU in companion animal medicine are underway and should include all members of the veterinary team, including veterinary support staff. Our objective was to describe knowledge and attitudes regarding AMU, AMR, and antimicrobial stewardship (AMS) in companion animal medicine among veterinary support staff professionals in the United States using an anonymous, online questionnaire. Additionally, we sought to explore veterinary support staff perceptions of their role in the antimicrobial drug (AMD) prescribing process. Veterinary technicians, nurses, assistants, client care representatives, and hospital managers (n=337) considered AMR a global concern (83.4%), and 40% reported receiving AMR education from their employer. Few (18.3%) were aware of AMS, with only 6.4% indicating that their clinic had an AMS program. Frequent involvement in the AMD prescribing process was reported (43.4%), but only 19.7% perceived involvement with AMS interventions. Approximately one-third of participants (34.9%) said that advice regarding the need for AMDs was routinely provided by staff to pet owners prior to veterinary consultation. Participants estimated that 82.6% of all AMD prescriptions were filled at the clinic as opposed to an outside pharmacy. Given their direct involvement in the AMD prescribing process and frequent interactions with pet owners, AMS should be emphasized to all veterinary staff. Involving support staff in AMS interventions is necessary to improve AMU in companion animal medicine.